Lily Quench and the hand of Manuelo - Prior, Natalie Jane, 1963- (New York : Puffin Books, 2004)
When Lily, Queen Dragon, and King Lionel follow Murdo in his flight to the Black Mountains, they become involved with a revolution led by the mysterious Manuelo.
9 13
Keywords: Revolutions -- Fiction; Dragons -- Fiction; Fantasy